Maternal antibody transfer to broiler progeny varies among strains and is affected by grain source and cage density - Leandro, N. M.; Ali, R.; Koci, M.; Moraes, V. [UNESP]; Eusebio-Balcazar, P. E.; Jornigan, J.; Malheiros, R. D.; Wineland, M. J.; Brake, J.; Oviedo-Rondon, E. O. (Poultry Science Assoc Inc, 2011)
Two experiments were conducted to examine the effects of broiler breeder dietary grain source and cage density on maternal antibody (MatAb) transfer to progeny in 2 genetic strains (A and B). Broiler breeders were assigned to 16 litter floor pens and fed either corn- or wheat-based diets. Breeders were administered 4 live vaccines against Newcastle disease virus (NDV). At 23 wk of age, pullets and cocks, which reflected the full BW distribution from each treatment, were moved to a cage breeder house and placed at 1 or 2 hens/cage. Breeders were artificially inseminated at 44 wk (experiment 1) and 52 wk of age (experiment 2). Eggs were collected for 8 d, incubated, and placed in individual pedigree bags at d 19 of incubation. Blood samples from 5 chicks per treatment combination were collected at hatch in both experiments. Spleen and bursa were collected from the same chicks for histomorphometry analyses in experiment 2. In the second experiment, 12 chicks per treatment were placed in cages. Progeny were provided diets based on the same grain (corn or wheat) as their parents. Serum samples were collected at 5, 9, and 13 d of age and analyzed for anti-NDV MatAb. Data were analyzed as a 2 x 2 x 2 factorial design considering strain, dietary grain source, and cage density as main factors. Interaction effects were observed in breeders and progeny. Experiment 1 showed that strain A chicks had lower levels of MatAb when hens were housed at 2 hens/cage rather than 1 hen/cage. The MatAb levels of strain B chickens were not affected by cage density in either experiment. Experiment 2 demonstrated similar effects of cage density on MatAb levels and the area of bursa follicles for both strains. Progeny of breeders fed corn-based diets had smaller spleen white pulp only when hens were housed at 2 hens/cage compared with 1 hen/cage. The results of these experiments suggest that breeder strain and cage-density conditions affected MatAb transfer to progeny and embryo development of spleen and bursa.
Keywords: breeder nutrition; broiler progeny; genetic strain; lymphoid tissue